Assessing the impact of mobile money transfer services on private credit and money transfer by commercial banks in Kenya. - Wamuthiani, Lynda Ndinda (Strathmore University, 2015)
This study explored whether mobile money transfer services as a technological advancement had any impact on private credit as measured by loans to the private sector and on commercial bank money transfer figures as measured by Real Time Gross Settlement (RTGS). The study adopts a time series analysis of the aggregate of loans to the private sector and RTGS for all commercial banks in Kenya between 2000 and 2013. The proxy for Mobile Money Transfer is MPESA transaction values captured since the inception of the service in Kenya in 2007. The magnitude and persistence of the impact of MPESA on private sector credit and RTGS is analyzed using a Vector Autoregressive (VAR) framework. The study revealed that the introduction and use of mobile money transfer services did not have any impact on private credit by commercial banks rather the positive correlation between the growth of the commercial bank assets and the growing use of mobile money was an indication of their fulfilling different roles in the financial services sector.